Implementasi Peraturan Daerah Kabupaten Lampung Utara Nomor 07 Tahun 2016 tentang Badan Permusyawaratan Desa dan Lembaga Kemasyarakatan di Desa Perspektif Fiqh Siyasah: Studi di Desa Tanjung Beringin Kecamatan Tanjung Raja - Cherly Sugistina; Nur Rahmah; Liky Faizal (Jurnal Hukum Lex Generalis, 2026)
Regional Regulation of North Lampung Regency Number 07 of 2016 concerning the Village Consultative Body and Village Community Institutions aims to position community institutions as partners of the village government in community empowerment. In practice, however, the implementation of Regional Regulation Number 07 of 2016 in Tanjung Beringin Village has not been carried out optimally. Karang Taruna, as one of the village community institutions, has not been able to perform its community empowerment function as mandated in Article 25 of the Regulation. This condition is reflected in the low level of youth participation, the lack of sustainable empowerment programs, weak coordination between the village government and Karang Taruna administrators and organizational activities that tend to be incidental and more oriented toward entertainment rather than social empowerment. Consequently, there is a discrepancy between the normative provisions that position Karang Taruna as a strategic partner of the village government in community development and the empirical realities found in the field. This study aims to analyze the implementation of Article 25 of the Regional Regulation concerning the role of Village Community Institutions and to examine its implementation from the perspective of fiqh siyasah. This research employs a qualitative method with an empirical approach through field research conducted in Tanjung Beringin Village, Tanjung Raja District. Data were collected through interviews, observations, and documentation. Interviews were conducted with the Village Head, the Head of Karang Taruna, Karang Taruna members, and members of the village community. The collected data were analyzed descriptively and analytically using the perspective of fiqh siyasah. The findings indicate that Karang Taruna in Tanjung Beringin Village has not optimally carried out its community empowerment function as mandated by Regional Regulation Number 07 of 2016. The activities conducted tend to be unsustainable, incidental and more oriented toward entertainment activities rather than community empowerment efforts. From the perspective of fiqh siyasah, this condition reflects the suboptimal implementation of the principles of trustworthiness (amanah), justice and public welfare (maslahah) in the management of village community institutions.